A Functional and Singable Musical Translation : The Finnish Translation of the Movie Encanto - Villa, Heidi (My University, 2022)
The topic of this study is musical translation and more specifically the achievement of a functional and singable translation. The aim is to discover the methods used for musical translation using Johan Franzon's (2021) six methods for analysing the relation between the original text and the translation. The methods, which Franzon applies to complete cover songs, are in this study applied to individual translation segments of songs, analysed row by row. These units were selected by following the pacing of the original lyrics and separating the lyrics and their translations into individual and clear units of text. The material of this study is the animated Disney musical Encanto (2021). The original language of the film is English, with some additional Spanish. The subject of the study is the Finnish translation of the dubbed songs, which also feature the Spanish language. The role of the Spanish language present in the translation is also analysed. The main results of this study aligned with Franzon's, as the largest number of translation units were near-enough translations. The second largest number of units were the near opposite, all new lyrics. As there is room for human error when classifying the material, future research could test this method using multiple researchers conducting the same analysis and develop further the selection of the material and definition of translation units to be analysed.
Keywords: musical, translation, musical theatre, song translation, lyrics, wordplay